2019
DOI: 10.1108/ejim-12-2018-0257
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and innovative work behavior

Abstract: Purpose The purpose of this paper is to investigate the effect of transformational leadership on employee’s innovative work behavior, and the mediating role of motivation to learn, and the moderating role of task complexity and innovation climate on the link between transformational leadership and innovative work behavior. Design/methodology/approach A questionnaire, designed as a self-reported survey, was distributed to full-time employees and their respective supervisors working in 35 firms (services and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
266
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 278 publications
(303 citation statements)
references
References 127 publications
22
266
1
14
Order By: Relevance
“…Our results might be influenced by unequal number of employees being rated by supervisors. However, this practice is in line with existing studies which examined the relationship between supervisor (e.g., leadership) and IWB using sample of employees with different numbers working under different supervisors (Afsar, Badir, & Bin Saeed, ; Gong, Huang, & Farh, ; Janssen, ; Masood & Afsar, ).…”
Section: Methodssupporting
confidence: 81%
“…Our results might be influenced by unequal number of employees being rated by supervisors. However, this practice is in line with existing studies which examined the relationship between supervisor (e.g., leadership) and IWB using sample of employees with different numbers working under different supervisors (Afsar, Badir, & Bin Saeed, ; Gong, Huang, & Farh, ; Janssen, ; Masood & Afsar, ).…”
Section: Methodssupporting
confidence: 81%
“…A 20‐item scale was taken from Multifactor Leadership Questionnaire (MLQ) Form 5× to measure transformational leadership, including idealized behaviors, idealized attributes, inspirational motivation, intellectual stimulation, and individualized consideration (Bass & Avolio, , p. 38). We converted these scales into one higher order factor which is consistent with recent empirical (Afsar et al., ) and theoretical developments (Zhang & Bartol, ) of transformational leadership. Exploratory factor analysis using the principal components method and varimax rotation was conducted on the 20 items to determine their factor structure.…”
Section: Methodsmentioning
confidence: 90%
“…First, our overall contribution is that we have built and tested a conceptual model that uniquely integrates transformational leadership theory with important innovation process theories. Second, transformational leadership influences employee innovative work behavior through psychological empowerment (Afsar et al., ) but, according to Zhang and Bartol (), the extent to which followers actually want to experience psychological empowerment has an impact. Therefore, this study introduced the moderating role of empowerment role identity and found that transformational leadership affects psychological empowerment strongly when nurses view empowerment as part of their role identities.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between transformational leadership (TFL) and individual, team, and organizational performance outcomes have been reported (e.g., Wang, In‐Sue, Courtright, & Colbert, ). In fact, transformational leaders increase employee creative performance (CP) by enhancing employee beliefs and motives and supporting employees in achieving higher‐level functioning (Afsar, Badir, & Saeed, ). Rosing, Frese, and Bausch's () meta‐analysis comparing leadership styles found that TFL was the strongest leadership style for increasing CP.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Burns’ () TFL theory posits that leaders can enhance beliefs and motives in their followers and support them in achieving higher‐level functioning. Thus, as a part of understanding predictors of creativity, a body of research has focused on the effect of TFL on individual (Si & Feng, ), group (Zheng, Khoury, & Grobmeier, ), and organizational (Afsar et al., ; Tienne & Mallette, ) CP. Specifically, research has found a positive association between leaders with a TFL style and CP produced by teams led by these leaders (Eisenbeiss & Boerner, ; Vaccaro, Jansen, Van Den Bosch, & Volberda, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%